LATE PREGNANCY OUTCOMES AMONG WOMEN WHO ATTENDED AND WOMEN WHO DID NOT ATTEND FIRST TRIMESTER ANTENATAL CARE VISITS IN A SUBURBAN REGIONAL HOSPITAL IN CAMEROON - Tsi N. Njim, MD (Global Health and Education Projects, Inc., 2016)
Background: Despite relatively high number of women who attend antenatal care (ANC) in Cameroon, there is an ever-increasing maternal mortality ratio, and pregnancy outcomes remain inadequate. A new suggested Optimal ANC Package includes attending ANC in the first trimester. This study assesses the overall ANC coverage, the percentage, and pregnancy outcomes among women who attended and did not attend ANC in the first trimester in the Buea Regional Hospital (BRH) in Cameroon. Methods: A cross-sectional study was carried out among 200 consenting pregnant women presenting for delivery at the BRH. A bivariate analysis was used to compare the frequencies of various pregnancy outcomes within the the two categories of women who attended and who did not attend first trimester ANC. Results: Ninety-six percent of the women attended at least 1 ANC visit with 20.5% of these women attending ANC in the first trimester and 60.2% attending at least 4 visits. Sociodemographic and obstetric factors were not found to be associated with attending ANC in the first trimester. Also, there was no statistically significant association between all the late pregnancy outcomes assessed and attending ANC in the first trimester. Conclusions and Global Health Implications: Trends in most sub-Saharan countries seem to suggest that most women do not attend first trimester ANC. This could have negative consequences on overall perinatal outcome. More user-friendly educational programs for women of childbearing age is required in such regions to address this situation.